Identification of risk factors about cardiovascular disease and diabetes mellitus among employees of selected banks in Indore, Madhya Pradesh - Pathak, Nischal; Pattnaik, Shweta; Chundawat, Bheru Singh; Chaturvedi, Dharmesh (International Journal Of Community Medicine And Public Health, 2022)
Background: Cardiovascular disease (CVD) remains the highest cause of mortality in India and the majority of the cases are due to risk factor that includes hypertension smoking diabetes mellitus. Sedentary lifestyle and desk job employees are more prone to such diseases. Therefore, present study aimed to assess the risk factors of cardiovascular diseases among bank employees. Methods: Quantitative exploratory research design was used to conduct the study. A sample of 98 bank employees was selected for the study using non probability convenient sampling technique from different branches of SBI Indore. Results: Risk score for cardio vascular disease among bank employees expressed in percentage calculated through the structured interview scheduled and Joint British Societies for the prevention of cardiovascular disease (JBS3) risk calculator. 83% participants were at <10% risk (low), 17% participants were at 10-19.9% (mild) risk, 0 participants were at 20-29.9% (moderate) risk and 0 participants were at ≥30% (high) risk. There was significant association between the risk score and selected socio demographic variable among bank employees. Conclusions: Study concluded that there was a mild to moderate risk of cardiovascular disease among bank employees. Hence, proper awareness regarding various risk factors of cardio vascular diseases can help in reducing such risk among bank employees and personnel with similar working pattern. Method Quantitative exploratory research design was used to conduct the study. A sample of 98 bank employees was selected for the study using non probability convenient sampling technique from different branches of SBI Indore. Results Risk score for cardio vascular disease among bank employees expressed in percentage calculated through the structured interview scheduled and Joint British Societies for the prevention of cardiovascular disease (JBS3) risk calculator. 83% participants were at < 10% risk (low), 15% participants were at 10-19.9% (mild) risk, 0 participants were at 20-29.9% (moderate) risk and 0 participants were at ≥ 30% (High) risk. There is signification association between the risk score and selected socio demographic variable among bank employees. Conclusion Study concluded that there was a mild to moderate risk of cardiovascular disease among bank employees. Hence, proper awareness regarding various risk factors of cardio vascular diseases can help in reducing such risk among bank employees and personnel with similar working pattern.